Loyalitas Pegawai Ditinjau dari Kecerdasan Emosional, Komitmen, Self Efficacy, dan Kompetensi (Studi Kasus pada KPPBC TMP B Surakarta) - Yesi Yeshinta; Sri Hartono; Istiatin Istiatin (Business Management Analysis Journal (BMAJ), 2020)
The purpose of this study was to determine the influence emotional intelligence, commitment, self efficacy, and competence towards employee loyalty at KPPBC TMP B Surakarta. This research is a quantitative research. The study population consisted of 101 employees at KPPBC TMP B Surakarta, but only 65 samples were taken. The data was collected by using a questionnaire. In this study, the data was analyzed using the classic assumption test, multiple linear regression analysis, t test, F test, and the coefficient of determination test. The results showed the F test (simultaneous) showed emotional intelligence, commitment, self efficacy, and competency simultaneously had a significant effect on employee loyalty. The results of the t test (partial) showed emotional intelligence had a negative and significant effect on employee loyalty in KPPBC TMP B Surakarta. Meanwhile commitment, self efficacy, and competence have positive effect on employee loyalty in KPPBC TMP B Surakarta individually (partially).